Geographies of postcolonialism spaces of power and representation - Sharp, Joanne P. (SAGE, 2009)
This textbook provides an introduction to the principal themes and theories relating to post-colonialism. Written from a geographical perspective, it includes extended explanations of the cultural aspects and the material aspects of post-colonialism.